2015
DOI: 10.1111/codi.12798
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat area is associated with a high risk for early postoperative recurrence in Crohn's disease

Abstract: A high VFA value is associated with postoperative recurrence of Crohn's disease and has clinical implications with respect to optimizing prophylaxis for each individual. However, further studies are needed to confirm the predictive role of this biomarker in a different data set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 24 publications
3
74
1
Order By: Relevance
“…19 Interestingly, a number of recent studies have also demonstrated an association between visceral adiposity and post-operative morbidity and disease recurrence in CD. 20,21 Because these prior studies have small sample sizes and limited information on other key risk factors, our analysis which benefited from nearly 500 well-characterized CD patients and carefully adjusted for important confounders significantly extends these prior findings. Moreover, to our knowledge this is the first study evaluating the interaction between visceral adiposity and genetic predisposition on risk of CD complications.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…19 Interestingly, a number of recent studies have also demonstrated an association between visceral adiposity and post-operative morbidity and disease recurrence in CD. 20,21 Because these prior studies have small sample sizes and limited information on other key risk factors, our analysis which benefited from nearly 500 well-characterized CD patients and carefully adjusted for important confounders significantly extends these prior findings. Moreover, to our knowledge this is the first study evaluating the interaction between visceral adiposity and genetic predisposition on risk of CD complications.…”
Section: Discussionmentioning
confidence: 55%
“…17 A number of prior studies have evaluated the impact of VAT on disease incidence and progression, however these studies have been limited by their sample size and lack of detailed information on important confounders such as smoking. 16,1821 In addition, prior studies have not accounted for the potential influence of genetic variants on the association between VAT and CD progression. The importance of genetics in disease progression has been highlighted by twin studies demonstrating similar disease phenotypes across identical twins as well as a recent study demonstrating the association between genetic variants and disease phenotypes in CD.…”
Section: Introductionmentioning
confidence: 99%
“…In quiescent CD, mesenteric hypertrophy does not seem to be a risk factor for disease relapse. 180 However, our recent study demonstrated that increased MAT was associated with increased risk for postoperative recurrence 196 and postoperative complications in patients with CD after ileocolonic resection. 197 The investigation of molecular mechanisms of adipose tissue remodeling will have clinical implications in the current and future treatment of CD.…”
Section: Mesenteric Fat In the Disease Course Of CDmentioning
confidence: 91%
“…In a retrospective cohort study of 114 paediatric patients with IBD (101 with Crohn’s disease), high VAT volume was associated with increased risk of penetrating or stricturing Crohn’s disease complications (OR 1.7, 95% CI 1.1–2.9), Crohn’s-disease-related hospitalization (OR, 1.9, 95% CI 1.2–3.4), shorter time interval to surgery (HR 1.4, 95% CI 1.0–2.0) and moderate–severe disease activity scores (OR 1.8, 95% CI 1.1–3.1), after adjusting for age and BMI 24 . High visceral fat area has also been associated with increased risk of recurrence of Crohn’s disease after surgical resection (endoscopic recurrence: HR 8.6, 95% CI 1.6–47.1; clinical recurrence: HR 2.6, 95% CI 1.0–6.7) 80 . Likewise, the metabolic consequences of obesity, in particular of visceral adiposity, have also been associated with IBD-related disease severity.…”
Section: Effect Of Obesity On Ibd Coursementioning
confidence: 99%